2016
DOI: 10.1016/j.wneu.2016.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of Adjacent Segment Degeneration in Patients Treated with Posterior Cervical Cages: 2-Year Follow-Up

Abstract: In the current study, 5.9% of subjects treated with posterior cervical cages placed bilaterally between the facet joints developed adjacent segment degeneration at 2 years. Mild progression of existing degeneration was observed in 11.8% of subjects. Further evaluation to establish long-term incidence is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Patient outcome was assessed with NDI in all studies, except for 3-which used NDI in addition to SF-12. 8,14,16 At 12-month follow-up, the earliest published series in the literature reported significant improvements in the NDI (64.9 to 16.3). Additionally, the SF-12 physical component score (PCS), and SF-12 mental component score (MCS) improved from 34.6 to 45.4 and from 40.7 to 51.4, respectively.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 98%
See 3 more Smart Citations
“…Patient outcome was assessed with NDI in all studies, except for 3-which used NDI in addition to SF-12. 8,14,16 At 12-month follow-up, the earliest published series in the literature reported significant improvements in the NDI (64.9 to 16.3). Additionally, the SF-12 physical component score (PCS), and SF-12 mental component score (MCS) improved from 34.6 to 45.4 and from 40.7 to 51.4, respectively.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 98%
“…Four of the included studies included patient reported outcomes (71.4%). 8,14,16,17 One study was a purely radiographic study 12 (14.3%) and another study was an analysis of a medical device registry (14.3%). 13 All studies, except 2, were limited to single-level interventions.…”
Section: Included Studies and Quality Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…An alternative surgical technique has been reported that involves placement of posterior cervical cages (PCC) between bilateral facet joints. This minimally disruptive technique has been shown to provide indirect decompression, is associated with a low complication profile [22], and high fusion rates [23] [24].…”
Section: Introductionmentioning
confidence: 99%